Peran Live Streaming, Flash Sale, dan Gratis Ongkir pada Pembelian Impulsif Gen Z - Pravitasari, Dea; Santi, Ira Nuriya; Fadjar, Adfiyani; Wirastuti, Wiri (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study explores the effects of live streaming, flash sales, and the free shipping tagline on Gen Z consumers impulse purchases of facetology products at Shopee. Research Methodology: Purposive sampling is one of the quantitative sampling strategies used in this study. In this study, the sample comprised 120 respondents. A Likert scale was used as a measurement tool in a questionnaire used to collect data SPSS. Results: The results of this study show that live streaming, flash sales, and the free shipping tagline, both partially and stimulatingly, contribute to and have a positive impact on impulse purchases. Marketing strategies using live streaming, flash sales, and free shipping taglines are effective in simulating impulse purchases, based on an R-squared of 58,9%. Conclusion: This study concludes that interactive promotional tools such as live streaming, limited-time flash sales, and attractive free shipping significantly drive Gen Z consumers’ impulse buying behavior on e-commerce platforms. These strategies enhance consumer engagement and create a sense of urgency that leads to higher spontaneous purchases, particularly of beauty and cosmetic products. Limitations: Sample capacity is one of the limitations of this study. The resulting findings may not fully reflect the behavior of all Shopee users or beauty product consumers in general. Contribution: This research examines Generation Z consumer behavior in e-commerce and provides insights that can be used by marketers to develop effective marketing strategies, particularly through the use of live streaming and free shipping tagline promotions to increase the sales of cosmetics products on digital platforms.